2008
DOI: 10.1002/jcb.21753
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of adipocyte differentiation by phytoestrogen genistein through a potential downregulation of extracellular signal‐regulated kinases 1/2 activity

Abstract: In the current study, we investigated the effects of genistein on adipogenic differentiation of mouse bone marrow-derived mesenchymal stem cell (BMSC) cultures and its potential signaling pathway. The terminal adipogenic differentiation was assessed by western-blotting analysis of adipogenic-specific proteins such as PPARγ, C/EBPα, and aP2 and the formation of adipocytes. Treatment of mouse BMSC cultures with adipogenic cocktail resulted in sustained activation of extracellular signal-regulated kinases 1 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…Reduced abdominal fat and mammary adipocyte size have previously been observed in the female mammary gland at PND50 after longer periods of developmental SPI exposure beginning with the dams during gestation (56). Isoflavones and E2 are both recognized to inhibit adipogenesis and reduce fat cell size (8,28,36,38,56). Reductions in adiposity might be mediated via isoflavone activation of a subset of estrogen receptor-mediated pathways or alternately through other pathways such as inhibition of sterol receptor element binding protein (SREBP-1c)-mediated fatty acid synthesis or activation of the nuclear receptor PPAR-␣ to increase fatty acid metabolism (44).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Reduced abdominal fat and mammary adipocyte size have previously been observed in the female mammary gland at PND50 after longer periods of developmental SPI exposure beginning with the dams during gestation (56). Isoflavones and E2 are both recognized to inhibit adipogenesis and reduce fat cell size (8,28,36,38,56). Reductions in adiposity might be mediated via isoflavone activation of a subset of estrogen receptor-mediated pathways or alternately through other pathways such as inhibition of sterol receptor element binding protein (SREBP-1c)-mediated fatty acid synthesis or activation of the nuclear receptor PPAR-␣ to increase fatty acid metabolism (44).…”
Section: Discussionmentioning
confidence: 89%
“…Genistein is a well-described inhibitor of the MAPK phosphatase Dusp1 (33,34), which was also reported to be downregulated by equol (4). Expression of the transcription factor Cebpa was also found to be reduced following genistein treatment (28,38). Dusp1 and Cebpa, as well as two other SPI downregulated genes in males, Aebp1 and Fgfr1, are positive regulators of ERK1/2-mediated adipogenesis (21,28,38,39,61).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Similarly, other research has shown that E and E-like compounds inhibited the DNA-binding activity of PPARγ and that nuclear extracts isolated from adipose tissues of ERβ-KO mice showed increased binding of endogenous PPARγ in comparison with wild-type mice [26] . PPARγ-binding activity was also markedly decreased in the phytoestrogen genistein-treated cells compared with untreated control [39] . The mammalian two-hybrid assay showed that E significantly decreased the troglitazone-induced CBP association in the presence of ERα or ERβ and that this effect was more prominent by ERβ.…”
Section: Discussionmentioning
confidence: 90%
“…[28][29][30] Inhibition of the ERK1/2 pathway can increase ALP activity, and that mineralization in skeletal muscle-derived stem cells leads to osteogenesis. 31 Hepatic differentiation is tightly regulated by cytokines and growth factors through signaling events.…”
mentioning
confidence: 99%